Perbaikan Sifat Fungsional Agar-Agar dengan Penambahan Berbagai Jenis Gum - Murdinah Murdinah; Ellya Sinurat (Jurnal Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2011)
ABSTRACT Agar-agar is widely used as an additive for food products. However, the application is still limited due to its low functional properties. Increasing functional properties of agar-agar was conducted by the addition of gums because they have synergism effect with phycocoloid. Research was conducted by formulation of agar-agar with other gums i.e. Arabic gum, guar gum, locust bean gum (LBG) and konjac. The ratios of agar-agar and gums in the experiment were 1:3, 1:1 and 3:1. Native agar-agar without addition of gums was used a control. Observations done to evaluate their functional properties were gel strength, elasticity, syneresis, viscosity, melting point, and gelling point. Results showed that the addition of LBG and konjac significantly increased agar-agar gel strength. LBG and konjac showed synergism effect on increasing agar-agar gel strenght. Gel strength of agar-agar added with konjac at a ratio of 1:1 increased from 493 g/cm 2 to2011 g/cm 2and added with LBG with ratio of 1:1 increased from 493 g/cm 2to 864 g/cm 2. Elasticity of agar-agar added with guar gum at a ratio of 3:1 increased from 45 mm to 47.90 mm. Guar gum, LBG and konjac showed synergism effect on increasing agar-agar viscosity. Viscosity of agaragar added with guar gum, LBG and konjac at a ratio of 1:3 increased from 101 cPs to 1880, 1610 and 5380 cPs respectively. The melting point of agar-agar added with arabic gum at ratio 1:3 of decreased from 56 o C to 48o C.